Povyšenie special'noj fiziceskoj rabotosposobnosti sportsmenov posredstvom primenenija relaksacionnych upražnenij - Denisenko, Y. P.; Gumerov, R. A.; Morozov, A. I.; Mardanov, A. Kh. (Teorija i Praktika fiziceskoj Kul'tury, 2018)
Presently the physical working capacity building practices in sports are dominated by the training and competitive load stepping methods that are efficient enough for the key mission albeit associated with high risks for the athletes` health. Moreover, the higher are the training scopes and intensities (which have virtually reached the natural limits in modern sports), the more severe are the injuries and health disorders. To analyze the sport-specific movement control and coordination, muscular contraction and relaxation mechanisms and the central nervous (CNS) and neuromuscular (NMS) system functionality under the study, we applied the Y.V. Vysochin computerized polymyographic method which has been successfully used to support the elite team trainings. About 600 differently skilled athletes were sampled for the new relaxation practice piloting experiments. It took many years of experiments for the authors to develop the key special relaxation methods and tools for athletic progress at every training process stage. The study data and analyses demonstrate the need for a new integrated training system for physical and functional progress applicable from the early training stages to secure a multisided progress with persistent improvements in the bodily relaxation and inhibition skills and processes and natural protection mechanisms - to form the most efficient type of long-term relaxation-driven adaptability and secure individual progress.